2015
DOI: 10.3109/19396368.2015.1088102
|View full text |Cite
|
Sign up to set email alerts
|

Impact of supplementary royal jelly onin vitromaturation of sheep oocytes: genes involved in apoptosis and embryonic development

Abstract: Optimizing culture conditions lead to the improvement of oocyte developmental competence and additives with anti-oxidative activity in culture media improved embryonic development. Royal jelly (RJ) is a product from the cephalic glands of nurse bees that has considerable health effects. The aim of this study was to investigate the effect of different concentrations of RJ on the maturation, cleavage, and blastocyst rates and gene expression in the oocyte and cumulus cells during in vitro maturation (IVM) of she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 50 publications
4
21
0
Order By: Relevance
“…In our study, supplementation of royal jelly to IVM medium has increased the rate at which oocytes reached MIIstage in a dose-dependent manner, although the cumulus expansion was not different from that of the control group. In agreement with our results, Valiollahpoor et al (2016) has reported higher maturation rates of sheep oocytes when cultured in the presence of royal jelly at various concentrations. The positive effect of royal jelly in improving COC maturation could be due to the various active compounds like proteins, essential amino acids (cystine, lysine and arginine), sugars (fructose, glucose, and sucrose), vitamins (A, B5, C, D and E), and lipids (Howe et al, 1985;Boselli et al, 2003;Kodai et al, 2007;Tamura et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…In our study, supplementation of royal jelly to IVM medium has increased the rate at which oocytes reached MIIstage in a dose-dependent manner, although the cumulus expansion was not different from that of the control group. In agreement with our results, Valiollahpoor et al (2016) has reported higher maturation rates of sheep oocytes when cultured in the presence of royal jelly at various concentrations. The positive effect of royal jelly in improving COC maturation could be due to the various active compounds like proteins, essential amino acids (cystine, lysine and arginine), sugars (fructose, glucose, and sucrose), vitamins (A, B5, C, D and E), and lipids (Howe et al, 1985;Boselli et al, 2003;Kodai et al, 2007;Tamura et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…The SDC2 gene is involved in cell proliferation and cytoskeletal organization [22]. Enhanced expression of GREM1, HAS2, PTGS2, and STAR in CC has been reported to be associated with better oocyte and embryo development in human, bovine, and sheep [6,7,20,31,39]. An association between the cumulus expression of SDC2 and oocyte quality is suggested previously [22].…”
Section: Discussionmentioning
confidence: 95%
“…Several cumulus expressed genes are crucial for oocyte maturation and development and assessment of their expression can provide a reliable method for choosing oocytes with greater potential for blastocyst formation and live birth [4]. The expression of gremlin 1 (GREM1), hyaluronan synthase 2 (HAS2), prostaglandin-endoperoxide synthase 2 (PTGS2), and steroidogenic acute regulatory protein (STAR) genes in CC correlates with the developmental ability of oocytes and morphology of embryos [5][6][7]. The receptors of FSH and LH are expressed in CC [8,9], and it is proposed that LH contributes towards oocyte maturation exclusively through the cumulus expressed receptors [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-apoptotic effect of RJ is supported by report of Karadeniz, A., et al, (2011) who suggest that RJ acts as anti-apoptotic agent and antioxidant when used in co-administration with cisplatin in kidney and liver [58]. In addition Valiollahpoor Amiri, et al (2016) report that RJ inhibit apoptosis by increasing the expression of BCL2 [59]. In present study we insight into the mechanistic pathway of RJ anti-apoptotic effect through following PI3K/AKT pathway and pro-apoptotic caspase-3 with deepen in was observed in RJ pretreatment also testosterone levels was restored to approach normal control levels.…”
Section: Discussionmentioning
confidence: 90%